Exercise tolerance and thermoregulatory responses during cycling in boys and men - Rowland, T.; Hagenbuch, S.; Pober, D.; Garrison, A. (Medicine & Science in Sports & Exercise, 2008)
Purpose: Physiological responses to exercise in the heat differ between prepubertal children and young adults. Whether these maturity-related variations imply lower exercise tolerance, inferior thermoregulation, and greater risk for heat injury in the child is uncertain. This study directly compared thermoregulatory and cardiovascular responses as well as endurance performance between prepubertal boys and adult males during steady-load cycling in moderately hot and cool ambient conditions with moderate humidity.